Espace de coworking - Clément Fouquet (Temporalités)
Seen as an index of the modern work, coworking spaces are often thought of as specific, external of mainstream institutions of work. Moreover, the literature has regularly associated them with emerging type of workers who were at once described as nomads. Based on a survey carried out in one of the most important business coworking spaces in Lille, this article examines the role of these spaces in the working lives of their users. It thus shows how these spaces are linked to other work spaces, be it in companies for salaried users or at home for the self-employed. The professional activity of these workers is thus split up and distributed among different spaces, the question then being how they can ensure the continuity of this activity. Two devices play a central role here: on the one hand, the layout of the coworking spaces and the services they offer, and on the other hand, information and communication technologies which ensure a permanent “virtual” link (at least for workers) with the partners in the activity, whatever the spot. So, coworking spaces can be considered as a technical device involved in the splitting up of the activity.